Evaluation of a Tutor-Led Social Work Student Placement Programme - (:unkn) unknown (Trinity College Dublin, 2025)
This evaluation examines a pilot tutor-led social work student placement programme implemented at St. James Hospital, Dublin, in partnership with Trinity College Dublin. The initiative was developed in response to a national and international crisis in securing sufficient, high-quality practice placements for social work students¿a mandatory component of professional qualification under CORU standards. Traditionally, placement provision has relied on individual practitioners assuming practice teaching roles alongside heavy caseloads, creating barriers to sustainability and consistency. The pilot introduced an agency-based social work tutor, seconded on a part-time basis for one placement cycle (September-December 2023), to support practice teachers, enhance student learning, and explore the feasibility of this model in a hospital setting. Using a mixed-methods design, the evaluation combined an online questionnaire (n=22) with semi-structured interviews (n=15) involving students, practice teachers, university tutors, and senior staff. Findings were overwhelmingly positive and indicate that the tutor role delivered significant benefits across multiple domains. For students, structured group learning sessions, tailored academic support, and participation in interprofessional education enhanced confidence, integration of theory and practice, and preparedness for professional roles. For practice teachers, the tutor streamlined induction processes, provided additional supervision and a ¿safety net¿ for resolving issues, and alleviated workload pressures¿factors that increased willingness to take on placements. Department-wide benefits included fostering a culture of practice education, raising the profile of social work within interdisciplinary teams, and promoting careers in medical social work. Challenges identified were primarily logistical (e.g., desk space, scheduling) rather than conceptual, and participants strongly endorsed the continuation and expansion of the tutor-led model. The evaluation concludes that agency-based tutor roles have strong potential to enhance both the quality and quantity of social work placements, aligning social work with other health professions where clinical tutor positions are well established. Recommendations include formalising tutor posts across hospital and interprofessional sites to support sustainable placement provision, strengthen university-agency collaboration, and advance workforce development.
PUBLISHED
This evaluation is highly relevant to public policy in health and social care workforce planning. Ireland has committed to expanding training places for Health and Social Care Professions (HSCPs), including social work, alongside targeted investment to support clinical placements and infrastructure. The report provides evidence that agency-based tutor roles can address systemic barriers to placement provision, ensuring compliance with CORU standards and sustaining quality as student numbers grow. Adoption of this model would operationalise recent government policy commitments by creating a scalable, cost-effective approach to placement delivery, strengthening interprofessional learning, and improving graduate readiness for complex healthcare environments. Establishing funded tutor posts aligns social work with other HSCP disciplines where clinical tutor roles are standard, supporting workforce development and service integration.
Keywords: Inclusive Society; Making Ireland; Inclusive research; Participatory evaluation; Social Services; Social work education, work practice teaching, clinical placements